Temporal readings of memory work in the prison memoir - Stevens, Garth (PINS-Psychology in Society, 2018)
[BOOK REVIEW] Suttner, R (2017) Inside apartheid’s prison, 2nd edition. Auckland Park: Jacana Media. ISBN 978-1-4314-2517-4. Pages 214 Writing an academic review of a memoir is a particularly difficult undertaking. On the one hand, it is a process requiring a critical appraisal of the scholarly contribution of the text to an extant knowledge base; but on the other hand also requires a certain fidelity to the phenomenology of authorial experience that is conveyed through this life story genre. When I was approached to write this review of Raymond Suttner’s Inside apartheid’s prison, I was initially somewhat hamstrung by these two tasks that can appear inimical to each other at times. But it soon struck me that I had in fact encountered the text on three distinct occasions, in discrete temporal moments, from the early 2000s to 2018. Each of these encounters provided me with a different understanding of the text, the authorial voice, the register of the subjects being textually produced, the context of textual production, and the possible interpretations from interlocutors who apprehended the narrative at these varying temporal moments.